2021
DOI: 10.1007/s00161-020-00967-0
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-based strain gradient plasticity theory to model size-dependent kinematic hardening effects

Abstract: A common belief in phenomenological strain gradient plasticity modeling is that including the gradient of scalar variables in the constitutive setting leads to size-dependent isotropic hardening, whereas the gradient of second-order tensors induces size-dependent kinematic hardening. The present paper shows that it is also possible to produce size-dependent kinematic hardening using scalar-based gradient theory. For this purpose, a new model involving the gradient of the equivalent plastic strain is developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Another possibility is to consider the gradient of the equivalent plastic strain instead of the cumulative one. This will cause size-dependent kinematic hardening effects, as recently demonstrated by Jebahi and Forest (2021).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another possibility is to consider the gradient of the equivalent plastic strain instead of the cumulative one. This will cause size-dependent kinematic hardening effects, as recently demonstrated by Jebahi and Forest (2021).…”
Section: Discussionmentioning
confidence: 79%
“…For instance, in the reduced-order micromorphic model, cumulative plastic slip is an always increasing variable irrespective of the loading direction, leading to size-dependent isotropic hardening. Jebahi and Forest (2021) recently showed that size-dependent kinematic hardening can be predicted in scalarbased strain gradient models by accounting for the gradient of the equivalent plastic strain which does not increase monotonically.…”
Section: Comparison Of Predicted Size Effectsmentioning
confidence: 99%
“…Results of subsection 4.1 are obtained assuming quadratic defect energy. Although widely used in the literature (Gurtin, 2002(Gurtin, , 2004Gurtin et al, 2007;Bardella, 2016, 2018;Jebahi and Forest, 2021), the pertinence of this form of defect energy in the context of gradient-enhanced plasticity is questioned by several authors (Svendsen and Bargmann, 2010;Cordero et al, 2010;Forest and Guéninchault, 2013;. The present subsection aims at investigating the effects of the proposed plastic slip gradient decomposition using less-than-quadratic defect energy (i.e., less-than-two defect energy index n).…”
Section: Case Of Non-quadratic Defect Energymentioning
confidence: 99%
“…Although offering a simplified modeling framework, these models can yield likely unacceptable behaviors with pathological mesh dependence for some problems (Niordson and Hutchinson, 2003). Higher-order SGP approaches substantially deviate from conventional plasticity by considering new higher-order stresses and additional equilibrium and boundary conditions (Fleck and Hutchinson, 1997;Aifantis, 1999;Gurtin, 2002Gurtin, , 2004Gurtin et al, 2007;Forest and Aifantis, 2010;Bardella, 2010;Forest and Bertram, 2011;Anand et al, 2012;Cordero et al, 2016;Forest, 2020;El-Naaman et al, 2019;Jebahi et al, 2020;Jebahi and Forest, 2021;Cai et al, 2021). It is nowadays widely accepted that higher-order SGP theories offer powerful modeling capabilities, making them the most commonly used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized mechanics has been widely investigated in the literature. It has been implemented for problems of elasticity [9][10][11][12][13]; plasticity [14][15][16][17][18][19]; damage modeling [20][21][22][23][24][25]; modeling metamaterials [26][27][28] such as pantographic structures [29][30][31], network materials [32], viscoelastic truss structures [33], bipantographic structures [34], second gradient fluids [35]; gradient-enhanced homogenization [36][37][38][39]; micropolar continua [40]; fracture mechanics [41]; biomechanics [42][43][44]; and anisotropic systems [45]. Parameter determination of generalized mechanics models has been studied for static and dynamic regimes in Shekarchizadeh et al [46,47], respectively.…”
Section: Introductionmentioning
confidence: 99%